2019
DOI: 10.1111/ans.15378
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic totally extra‐peritoneal groin hernia repair with self‐gripping polyester mesh: a series of 780 repairs

Abstract: Background: Laparoscopic groin hernia repair is an increasingly common procedure with benefits of reduced post-operative pain and infection. Post-operative chronic pain remains an ongoing concern in about 10% of patients. Parietex ProGrip™, a polyester self-gripping mesh, has a theoretical benefit of avoiding tacks for mesh-fixation. This case series reflects our long-term experience of this technique. Methods: We conducted a retrospective case series from November 2011 to December 2017. Patients were identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 26 publications
4
8
1
Order By: Relevance
“…Common perioperative complication rates in inguinal hernia procedures are low, Stavert et al reported, in 780 laparoscopic inguinal hernia repairs, a complication rate of 0.13–1.67% being seroma (1.41%), hematoma (1.41%) and surgical site infection (SSI) (0.13%) the most frequently found 31 . Results similar to those were found in our study with a slightly higher presence of seroma but no presence of SSI (Seroma 2.1%, hematoma 1.45% and SSI 0%) 21 , 32 , 33 . In terms of SSI, adding clean contaminated procedure to hernia inguinal repair still remains controversial due to believed aggregated risk, nevertheless, as Quezada et al described in 21 patients who underwent concomitant laparoscopic hernia repair and cholecystectomy, we found lower incidence of SSI 34 .…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Common perioperative complication rates in inguinal hernia procedures are low, Stavert et al reported, in 780 laparoscopic inguinal hernia repairs, a complication rate of 0.13–1.67% being seroma (1.41%), hematoma (1.41%) and surgical site infection (SSI) (0.13%) the most frequently found 31 . Results similar to those were found in our study with a slightly higher presence of seroma but no presence of SSI (Seroma 2.1%, hematoma 1.45% and SSI 0%) 21 , 32 , 33 . In terms of SSI, adding clean contaminated procedure to hernia inguinal repair still remains controversial due to believed aggregated risk, nevertheless, as Quezada et al described in 21 patients who underwent concomitant laparoscopic hernia repair and cholecystectomy, we found lower incidence of SSI 34 .…”
Section: Discussionsupporting
confidence: 91%
“…Both scenarios presented are congruent with reported results in literature, Mitura et al in a study with 1647 patients found that greater pain was reported in patients more active professionally or those who performed heavily manual tasks, as our cases 31 , 43 . In respect of pain, results of our study are affected because a small percentage of patients completed a long time follow up (5 year evaluation), chronic pain is lower compared to similar studies, showing rates of 3.5% (with mesh) and 2.9% (without mesh) 21 , 29 , 36 .…”
Section: Discussioncontrasting
confidence: 75%
See 3 more Smart Citations